CORPUS-BASED ANALYSIS OF ACADEMIC ENGLISH VOCABULARY IN STUDENT WRITING - Boboniyozova Iroda Qurboniyozovna (Bright Mind Publishing, 2025)
This article investigates the corpus-based analysis of academic English vocabulary in student writing, with a particular focus on identifying patterns, frequency, and lexical sophistication in the written works of undergraduate learners. Academic writing is a cornerstone of higher education, and mastery of academic vocabulary plays a vital role in the development of students’ critical thinking, communicative competence, and scholarly expression. However, many students face challenges in employing appropriate vocabulary, often relying on limited lexical resources or general-purpose language that does not adequately reflect academic conventions. To address this issue, corpus-based methodologies provide systematic and empirical tools for analyzing large samples of texts, allowing researchers to uncover trends in lexical usage and identify gaps in learners’ academic vocabulary. The present study is based on a self-compiled corpus of student essays written in English, covering diverse subjects within the humanities and social sciences. Using frequency counts, keyword analysis, and lexical profiling, the research examines how effectively students utilize academic vocabulary and compares their usage with reference corpora such as the Academic Word List (AWL) and British Academic Written English (BAWE) corpus. Findings suggest that while students demonstrate awareness of academic vocabulary, their usage tends to be uneven, with frequent overuse of certain high-frequency academic words and underuse of discipline-specific terminology. The study highlights the implications of these patterns for teaching academic writing, arguing that corpus-based approaches can inform targeted instruction that strengthens students’ lexical repertoire and supports more precise, coherent, and discipline-appropriate writing practices. Ultimately, this research emphasizes the importance of corpus linguistics as a methodological framework in applied linguistics and pedagogical contexts, offering both diagnostic and pedagogical insights for enhancing academic writing instruction at the university level.
Keywords: Academic vocabulary, corpus linguistics, student writing, lexical profiling, academic word list, language pedagogy.